2016
DOI: 10.1016/j.jval.2016.03.1393
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Safety Of Paroxetine And Other Ssris For The Risk Of Hip Fracture In Elderly Nursing Home Residents With Depression

Abstract: A183outcomes. One-way, two-way, and probabilistic sensitivity analyses were used to examine uncertainty in the estimates. Results: Clozapine dominated the three therapies it was compared to and had negative ICERs compared to each of these therapies: -£8,773/QALY, -£20,659/QALY, and -£2,226/QALY, compared to olanzapine, quetiapine, and risperidone respectively. The results from the one-way and two-way sensitivity analyses suggested the findings were insensitive to changes in single model parameters of the top f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…No relevant randomized controlled studies were found. Sixteen studies were included from the previous systematic review, and 17 studies were identified as new in the databases (Figure ) …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No relevant randomized controlled studies were found. Sixteen studies were included from the previous systematic review, and 17 studies were identified as new in the databases (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…The studies we found were published between 1998 and 2016, with 11 studies since 2013 . Two studies were reported across multiple articles and each was treated as a single distinct study: Vestergaard et al and Souverein et al One study reported results from both a cohort and a nested case‐control analysis .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations